To pay or not to pay? handling crowdsourced participants who drop out from a research study - Benbunan-Fich, Raquel (Ethics and information technology, 2023)
This article examines whether a crowdsourced research participant who quits a study before its completion should receive any monetary compensation. The study is focused on participants recruited from Amazon Mechanical Turk, the most widely used crowdsourcing platform, and examines the tensions between participants’ rights and research objectives when online labor markets are used to recruit research participants. The discussion is informed by the recent literature on online research with crowdsourced samples, evidence from human subjects’ practices at top US universities, and an ethical analysis based on distributive justice and consequentialism. The results indicate that compensating crowdsourced research subjects who fail to complete their participation jeopardizes the benefits of many who dutifully participate and undermines the overall value of the research enterprise for advancing knowledge. By examining the issue of payment for crowdsourced participants who drop out, this article sheds light on modern ethical issues in online research and offers practical recommendations for researchers and ethics scholars.